Mediation of Buying Interest on the Relationship of Green Products to Purchase Decisions During the New Normal: Evidence from MSME Consumers in East Binjai Regency - Nel Arianty; Rini Astuti; Sri Endang Rahayu; Edisah Putra Nainggolan; Arif Pratama Marpaung (Institute of Computer Science (IOCS), 2022)
The author's purpose is to research to determine the effect of Green Products on Buying Decisions, determine the effect of Green Products Buying Interest, determine the effect of Buying Decisions on Buying Interest, determine the effect of Green Products on Buying Decisions mediated by Buying Interest in the New Normal Period Case Study on MSME Consumers East Binjai District. The approach used in this study is associative. The population in this study is the Consumers of SMEs in the District of Medan Timur. While the sample that meets the criteria for sampling the withdrawal of observations made is 100 people using non-probability sampling. The data collection technique in this study uses a questionnaire technique. The data analysis technique in this study uses Path Analysis, Partial Least Square (PLS). Data processing in this study using the SmartsPLS 3.0 software program. the results of testing the first and second hypotheses show that the Green Product on Buying Decision and Green Product on Buying Interest in the New Normal Period Case Study on MSME Consumers in East Binjai District is accepted. In the third and fourth hypotheses, Buying Decisions on Buying Interest and Green Products on Buying Decisions are mediated by Buying Interest in the New Normal Period.